Current Income Tax Disclosures in Separate Financial Statements of IFRS Adopters in Slovakia - Tumpach, Miloš, 1970-
Pravidlá zdaňovania pre používateľov IFRS na Slovensku (č. 431/2002 zb. z., paragraf 17).